Clinical and pathological features of toxoplasmosis in free-ranging common wombats (Vombatus ursinus) with multilocus genotyping of Toxoplasma gondii type II-like strains. Issue 2 (April 2015) - Donahoe, Shannon L.; Šlapeta, Jan; Knowles, Graeme; Obendorf, David; Peck, Sarah; Phalen, David N.
Abstract: Toxoplasma gondii is a cosmopolitan zoonotic protozoan parasite with the capacity to infect virtually any warm blooded vertebrate species. Australian native marsupials are thought to be highly susceptible to toxoplasmosis; however, most reports are in captive animals and little is known about T. gondii associated disease in free-ranging marsupials, including wombats ( Vombatus ursinus ). This study describes the clinical and pathological features of eight cases of toxoplasmosis in free-ranging common wombats in Tasmania and New South Wales (NSW) from 1992 to 2013, including a morbidity and mortality event investigated in the Southern Highlands NSW in the autumn of 2010. The diagnosis of T. gondii infection was confirmed using either immunohistochemistry, molecular diagnostics or both. Utilizing the combination of direct DNA sequencing of B1, SAG1, 5′- and 3′-SAG2, alt.SAG2, SAG3, BTUB, GRA6, c22-8, c29-2, L358, PK1 and Apico DNA markers and virtual RFLP to genetically characterize two of the T. gondii strains, we found a nonarchetypal type II-like strain (ToxoDB PCR-RFLP genotype #1) and an atypical type II-like strain (ToxoDB PCR-RFLP genotype #3) to be the causal agents of toxoplasmosis in wombats from the 2010 morbidity and mortality event. This study suggests that T. gondii may act as a significant disease threat to free-ranging common wombats. Our findings indicate neurologic signs are a very common clinical presentation in common wombats with toxoplasmosis and T. gondii infection should be considered as a likely differential diagnosis for any common wombat exhibiting signs of blindness, head tilt, circling and changes in mentation. Graphical abstract: Highlights: A type II-like strain Toxoplasma gondii in wombats from Australia Toxoplasmosis in wombats associated with blindness and central nervous system signs. Toxoplasma gondii may act as a significant disease threat to free-ranging wombats.